Bringing rigor in contextual objectivity: lessons from applying feminist lens in scoping the evidence on girlhood studies in Indonesia - Kusumaningrum, Santi; Tieken, Shaila; Adhi, Andrea Andjaringtyas; Nisa, Siti Ainun; Sari, Widi Laras; Beta, Annisa R. (Frontiers in Research Metrics and Analytics, 2024)
This perspective paper contemplates the nuances of engaging with literature ethically in conducting a scoping review based on the researchers' project on girlhood studies in Indonesia. We assert that the ethical perspective extends beyond conventional primary data collection from human participants, further emphasizing the essence of a feminist methodology in this scholarly investigation. We discuss the interplay between the role of rigor and the dynamics of power relations in research, shedding light on reconciling between the pursuit of facts and acknowledgment of biases in knowledge production. This reflection offers insights into the methodological process and the researcher's role, contributing to the broader discourse on how research can effectively address issues of gender equity and social inclusion. Through this paper, we underscore the necessity of an intentional approach in unifying the domains of science and advocacy because only then can we truly catalyze transformative change. In doing so, we seek to foster a more comprehensive, objective, and empathetic understanding of the researched: in this case, the experiences of girls and young women –and, by extension, marginalized individuals in Indonesia and beyond.